Pigment and Nutritional Value of Spirogyra spp. in Sakon Nakhon, Nakhon Phanom and Mukdahan Provinces - Sitthiwong, Nopparut (Progress in Applied Science and Technology, 2019)
Edible freshwater macroalgae, Spirogyra spp. (Division Chlorophyta) are normally found in natural water sources and local markets, and are commonly consumed as a traditional type of food in north-eastern Thailand. Spirogyra spp. has been found to possess high nutritional value and contain various bioactive compounds. The focus of this research study was to examine the pigments and to assess the nutritional value of the Spirogyra spp. samples collected from 12 water resources of Sakon Nakhon, Nakhon Phanom and Mukdahan Provinces. The samples collected from each sampling site were dried and the pigment quantity and nutritional value were analyzed. The highest quantity of chlorophyll a, b and the carotenoid content were recorded at 4.067, 1.716 and 1.209 mg/g of cell dry weight, respectively. The samples were tested for their basic nutritional value and the highest values of ash, fat, moisture, protein, carbohydrate and energy were recorded at 17.37, 5.51, 14.90, 22.77, 67.13 g/100g and 363 kcal/100g, respectively. Thus, the results of this study support the possibility of using Spirogyra spp. as a food supplement and antioxidant products.